«Բանք իմաստասիրաց աւգտակարք եւ պիտանացուք» - Պողոսյան, Ռուզան
Armenian manuscripts of the Sayings of Philosophers have remained largely unexplored by scholars, unlike those in other languages. This is our first attempt to present an earlier version of the text, dating to the 13th century, which was either fully or partially copied in 14th-century manuscripts. A comparative analysis of the text reveals that many of the sayings exhibit parallels with the collection known as the Corpus Parisinum. We hypothesize that a selection of these sayings may have been compiled in the 11th or 12th centuries. It is also possible that this selection was made by the Armenian clergy, at the request of either the clerical elite or the patron of these manuscripts. Армянские тексты «Изречений философов», в отличие от аналогичных сборников на других языках, остаются в значительной степени неисследованными. В статье представлена наиболее ранняя редакция текста, датируемая XIII веком и либо полностью, либо частично воспроизведенная в рукописях XIV века. Сравнительный анализ текста показывает, что многие из изречений имеют параллели в сборнике, известном как Corpus Parisinum. Мы предполагаем, что подборка этих изречений могла быть составлена в XI или XII веках. Также возможно, что эта подборка была сделана по просьбе церковной элиты или заказчиков рукописей.
Keywords: Հրապարակումներ; Ձեռագրական մշակույթ